Proliferasi Gerakan Islam Konservatif Pasca-Otoritarianisme Orde Baru - Marom, Ahmad Anfasul; Vebriandy , Willy (Universitas Brawijaya, 2025)
This article examines the proliferation of conservative Islamic movements in Indonesia following the collapse of the New Order in 1998. Drawing on a qualitative approach grounded in comprehensive literature analysis, the study employs political opportunity structure theory to demonstrate how the Reformasi Era opened new institutional and discursive spaces for previously marginalized conservative Islamic groups to renegotiate their position within national politics. The resurgence of these movements materialized in three principal forms: the proliferation of Islamic political parties in the 1999 general elections; the revitalization of debates on the Jakarta Charter during the constitutional amendment process; and the expansion of Sharia-inspired regional regulations across a wide range of local governments. The article argues that decentralization under the Reformasi Era inadvertently created enabling political opportunities that facilitated the consolidation, institutionalization, and public expansion of conservative Islamic activism in post-authoritarian Indonesia